АНАЛИЗ ТЕМПЕРАТУРНОГО ПОЛЯ РОТОРА ТУРБОГЕНЕРАТОРА МОЩНОСТЬЮ 300 МВт ПРИ АСИММЕТРИИ ОХЛАЖДЕНИЯ ПАЗОВОЙ ЗОНЫ - Кучинский , К.А. (Інститут електродинаміки НАН України, Київ, 2013)
By means of a finite-elements method temperature fields on polar division of a rotor of turbogenerator ТГВ-300-2 in a nominal mode are investigated at infringements of symmetry of direct hydrogen cooling in channels of a winding of excitation. It is shown, at what quantity of "defective" channels the maximum temperature of isolation of a winding of a rotor exceeds maximum permissible magnitude. Magnitudes of internal stresses of compression in copper of convolutions on superheated sections of a winding are defined. It is defined, at what temperatures mechanical stresses surpass a copper yield stress. Comparison of values of experimental and settlement thermal and thermomechanical parameters on physical model of the rod of a winding of the stator powerful ТГ is spent. References 16, tables 2, figures 5.